PROSES ADAPTASI MIGRAN SIRKULER : KASUS MIGRAN ASAL KOMUNITAS PERKEBUNAN THE RAKYAT CIANJUR, JAWA BARAT - TARIGAN, HERLINA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 2 Juli 2004)
Circular migrant adaptation process: Case of migrants originated from Tea Smallholder Plantation Community in Cianjur, West Java. Value of work orientation changes from agriculture towards non-agriculture has caused higher population mobility from rural to urban areas. Sociologically, this geographical or spatial mobility is also a socio-cultural mobility from traditional agriculture towards modern industry. Migrants should be adaptive to new situation so that the purpose of migrating would be achieved. The objectives of the study are to investigate: (1) influencing factors of population migration; (2) Adaptation process of migrants originated from smallholder plantation community in Cianjur working in Tangerang Industrial Areas. The study applied qualitative method with case study strategy. The results of the study showed that economic and social factors pushed the migration cases complimentarily. Adaptation process by maintaining “in group feeling” succeeded in providing sense of serenity and comfort ability although it seemed to get acculturation process slowed down. Orientation of working for the future directed the migrants to keep making relation with their relatives or their hometown communities
Keywords: Adaptation Process, Circular Migrant, Plantation Community.